(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Article peer reviewed SUMMARY: 1. Problem description – 2. Practical Importance of the issue of the content of “Human Being” Concept – 3. Conceptual Approaches to Interpretation of the Concept of “Human Being” – 4. Conclusion.